METODE KOMUNIKASI PENYULUHAN PADA PETANI SAWAH - Anuar Rasyid (Universitas Riau, 2012)
Method of Extension in Farmers' Fields of Communication. The purpose of this research isto analys the extension method of Information Extension Office (BIP). This is a qualitative research in theIllumination of Communication Method for Rice Farmer in the Information Extension Office (BIP)Bangkinang Barat Kampar with the data collection technique Participant Observation, interview, anddocumentation. After the data is collect, the writer analys the data using Interactive Model Analysis. Theresult of the research, the role of counselor in the middles of farmers needed a lot to assist in the developingagribusiness in farmer people or farmer group. By the present of counselor will bring large affect tocommunity, which before the present of counselor, the way of land management was not appropiate witsthe knowledge which though by the counselor through agriculture.